Modeling Sovereign Yield Spreads: A Case Study of Russian Debt - Duffie, Darrell; Pedersen, Lasse Heje; Singleton, Kenneth J. (Journal of Finance, 2003)
We construct a model for pricing sovereign debt that accounts for the risks of both default and restructuring, and allows for compensation for illiquidity. Using a new and relatively efficient method, we estimate the model using Russian dollar‐denominated bonds. We consider the determinants of the Russian yield spread, the yield differential across different Russian bonds, and the implications for market integration, relative liquidity, relative expected recovery rates, and implied expectations of different default scenarios.